2013
DOI: 10.4103/0250-474x.117433
|View full text |Cite
|
Sign up to set email alerts
|

Acute and subchronic toxicity study of Tamra bhasma (incinerated copper) prepared from Ashodhita (unpurified) and Shodhita (purified) tamra in rats

Abstract: The use of metals in traditional medicines is very often seen as matter of concern these days, especially the Bhasma preparations which are always under stringent observations for containing highly reactive inorganic elements such as lead, mercury, arsenic and others. One of the Bhasma extensively used in routine Ayurvedic practice is Tamra (copper) bhasma. If it is not prepared properly or Shodhana procedure is not done properly, it acts as a poison. To indicate its toxic potential, Ashtamahadoshas (eight maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 10 publications
0
13
0
3
Order By: Relevance
“…Previous studies reported safety of TB in animal models [7] , [8] . Role of Shodhana in safety of TB was also reported in animals [9] . Though number of studies have been carried out in direction of safety of Bhasmas , concerns are always being raised on ayurvedic formulations for the presence of heavy metals [10] , [11] .…”
Section: Introductionmentioning
confidence: 86%
“…Previous studies reported safety of TB in animal models [7] , [8] . Role of Shodhana in safety of TB was also reported in animals [9] . Though number of studies have been carried out in direction of safety of Bhasmas , concerns are always being raised on ayurvedic formulations for the presence of heavy metals [10] , [11] .…”
Section: Introductionmentioning
confidence: 86%
“…Man geht unter anderen davon aus, dass es sich bei dem toxischen Quecksilber vor allem um Methylquecksilber handelt, bei dem gereinigten dagegen um Quecksilbersulphat. Tatsächlich gibt es experimentelle Hinweise, dass bei korrekter "Entgiftung" der Schwermetalle die sonst zu erwartenden Zeichen einer Intoxikation auch bei hoher Dosis nicht entstehen [4,[11][12][13][14][15][16] Da man chemisch ein "gereinigtes" von einem "nicht gereinigten", detoxifizierten Metall nicht trennen kann, fehlen bis heute eindeutige Parameter, mit denen ein potenziell heilendes Schwermetall von einem giftigen unterschieden werden kann. Zudem sind die Toxizitätsstudien, auch aus präklinischer Forschung, bislang nicht hinreichend, um eine gefahrlose Verabreichung dieser Medikamente zu garantieren.…”
Section: Schwermetalle In Rasa-medikamentenunclassified
“…In Indien sind trotz geringerer Pharmakovigilanzmechanismen nur wenige Einzelfälle beschrieben, bei denen Gesundheitsschäden durch schwermetallhaltige Medikamente hervorgerufen wurden [17][18][19]. Stattdessen richtet sich die dortige Forschung auf die korrekte Herstellungsweise, Wirksamkeit und Ungiftigkeit der rasa-Medikamente [11][12][13][14][15][16].…”
Section: Diskussion Um Die Toxizität In Der Forschungunclassified
“…To name a few, toxicity studies of Abhraka Bhasma , Tamra Bhasma , Trivanga Bhasma , Yashada Bhasma , Shilasindura , etc., and many more have concluded their safety at therapeutic dose levels. [ 4 5 6 7 8 ]…”
Section: Introductionmentioning
confidence: 99%